Activation of the immune system of pigs and its requirement of methionine, threonine and tryptophan - Martínez-Aguilar, Marco V. (2020)
The high animal densities used in swine production are a challenge to their sanitary status, favoring the spread of diseases. These diseases cause metabolic changes, increasing energy expenditure and shifting nutrients from maintenance, growth and tissue repair towards the immune system. Therefore, the objective of this literature review was to assess the main mechanisms of immune activation in sanitary-challenged pigs and the associated requirements of certain amino acids, in order to consider the immune system as a key part of an effective nutrition. The activation of the immune system induces the release of pro-inflammatory cytokines, which stimulate the synthesis of acute phase proteins. The synthesis of acute phase proteins increases the requirement of certain amino acids. If the requirement of amino acids is above their serum availability, muscle protein catabolism is induced; and the resulting amino acids can be used as energy source and antioxidant precursors. Methionine, threonine and tryptophan are the main amino acids with influence on the immune response to clinical and subclinical diseases. In conclusion, a diet that only supplies maintenance and growth requirements when there is an immunological challenge, without considering the requirements of the immune system, can cause a nutritional deficiency and a reduction in animal performance. Therefore, increasing the supplementation of the amino acids related to the immune system above the recommended ideal protein profile should be evaluated, especially under sanitary stress conditions.